2013
DOI: 10.1136/emermed-2013-202536
|View full text |Cite
|
Sign up to set email alerts
|

Paramedic Initiated Lisinopril For Acute Stroke Treatment (PIL-FAST): results from the pilot randomised controlled trial

Abstract: BackgroundHigh blood pressure (BP) during acute stroke is associated with poorer stroke outcome. Trials of treatments to lower BP have not resulted in improved outcome, but this may be because treatment commenced too late. Emergency medical service staff (paramedics) are uniquely placed to administer early treatment; however, experience of prehospital randomised controlled trials (RCTs) is very limited.MethodsWe conducted a pilot RCT to determine the feasibility of a definitive prehospital BP-lowering RCT in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 17 publications
4
56
0
Order By: Relevance
“…Given that transdermal GTN is inexpensive (≈£5 per patient), safe, widely available and can be easily administered before hospitalization or brain imaging, these results, and those from the RIGHT pilot trial and a meta-analysis of preclinical stroke studies, 12,17 justify a further large study: the RIGHT-2 trial (http://right2-trial.org), which will further assess the safety and efficacy of GTN in 850 patients with ultra acute stroke who are recruited by paramedics in the prehospital ambulance environment using a protocol that builds on the earlier Rapid Intervention With Glyceryl Trinitrate in Hypertensive Stroke Trial (RIGHT), and Field Administration of Stroke TherapyMagnesium (FAST-Mag) trial. 17,42,43 SUPPLEMENTAL MATERIAL Supplemental Table I Numbers needed (NNT) to treat with 95% confidence intervals for outcomes at day 90 with analysis using ordinal and binary data. NNT is the number of people who need to be treated for one to change an outcome state.…”
Section: Strokementioning
confidence: 99%
“…Given that transdermal GTN is inexpensive (≈£5 per patient), safe, widely available and can be easily administered before hospitalization or brain imaging, these results, and those from the RIGHT pilot trial and a meta-analysis of preclinical stroke studies, 12,17 justify a further large study: the RIGHT-2 trial (http://right2-trial.org), which will further assess the safety and efficacy of GTN in 850 patients with ultra acute stroke who are recruited by paramedics in the prehospital ambulance environment using a protocol that builds on the earlier Rapid Intervention With Glyceryl Trinitrate in Hypertensive Stroke Trial (RIGHT), and Field Administration of Stroke TherapyMagnesium (FAST-Mag) trial. 17,42,43 SUPPLEMENTAL MATERIAL Supplemental Table I Numbers needed (NNT) to treat with 95% confidence intervals for outcomes at day 90 with analysis using ordinal and binary data. NNT is the number of people who need to be treated for one to change an outcome state.…”
Section: Strokementioning
confidence: 99%
“…7 Recent pilot studies have assessed the feasibility of a prehospital BP-lowering strategy in patients with acute stroke symptoms using topical glyceryl trinitrate 8 and sublingual lisinopril. 9 At this point, however, the natural history of BP in the prehospital setting in patients with acute stroke symptoms is poorly understood. In contrast, the course of BP after hospital admission has been well described.…”
mentioning
confidence: 99%
“…Patients in Combined Table 2 Trials that did not require written consent Treatment With Alteplase (Rt-PA) and Cerebrolysin ® in Acute Ischemic Hemispheric Stroke (CERE-LYSE) and Paramedic Initiated Lisinopril For Acute Stroke Treatment (PIL-FAST) had to provide subsequent written informed consent for inclusion in the trial. 26,37 In The Pre-Hospital Acute Neurological Therapy and Optimization of Medical Care in Stroke Patients Study (PHANTOM-S), only deidentified data could be gathered from individuals unable to give informed consent; later telephone follow-up at 3 months required written informed consent, as mandated under German law. 9 In the Rapid Intervention with Glyceryl Trinitrate in Hypertensive Stroke Trial (RIGHT), written informed consent was required by the patient or proxy at the hospital, after the first treatment dose had been given in the ambulance.…”
mentioning
confidence: 99%
“…On univariable analysis (of the entire dataset, including these 2 outlier trials), we found that trials of prehospital interventions were less likely to require written informed consent (p , 0.01). The prehospital interventions included 2 German trials of mobile stroke units with on-board imaging and thrombolysis capabilities (the only 2 cluster-randomized trials in this review), 8,9 a Swedish trial in which participants in the intervention arm were assigned a higher prehospital priority level by the emergency dispatch center, 28 and 3 trials with paramedic-initiated therapies: lisinopril (UK), 37 ischemic preconditioning (Finland), 39 and glycerol trinitrate (UK). 40 Of these prehospital trials, only one required written informed consent en route to the hospital.…”
mentioning
confidence: 99%
See 1 more Smart Citation